1997
DOI: 10.1037/0021-9010.82.2.281
|View full text |Cite
|
Sign up to set email alerts
|

Managerial self-awareness in high-performing individuals in organizations.

Abstract: Individual differences in the construct of managerial self-awareness (MSA) -operationalized as congruence between self and direct reports' behavioral ratings-were examined in 134 high-performing (HP) and 470 average-performing (AV) managers obtained from 4 independent datasets. Results based on several different approaches to measuring ratings agreement indicated that HPs were significantly more managerially self-aware compared with AVs. This relationship was consistent regardless of data source, organization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
196
2
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 223 publications
(212 citation statements)
references
References 64 publications
10
196
2
2
Order By: Relevance
“…In addition to enhancing the managers' self-awareness, we also propose that an important side effect of the coaching that accompanies the 360-degree feedback can be a positive impact on the attitudes of the managers and their employees (Church, 1997;Rogers, Rogers, & Metlay, 2002;Walker & Smither, 1999). In other words, achieving the reduced perceptual discrepancies is not an end in itself; just as important is the positive impact it can have on personal and employee outcomes (Hollenbeck, 1989;Phillips, Hollenbeck, & Ilgen, 1996).…”
Section: Background Of the Studymentioning
confidence: 99%
“…In addition to enhancing the managers' self-awareness, we also propose that an important side effect of the coaching that accompanies the 360-degree feedback can be a positive impact on the attitudes of the managers and their employees (Church, 1997;Rogers, Rogers, & Metlay, 2002;Walker & Smither, 1999). In other words, achieving the reduced perceptual discrepancies is not an end in itself; just as important is the positive impact it can have on personal and employee outcomes (Hollenbeck, 1989;Phillips, Hollenbeck, & Ilgen, 1996).…”
Section: Background Of the Studymentioning
confidence: 99%
“…This difference may also be a result of the raters actually observing different behavior (London & Beatty, 1993) or the individual displaying different behaviors in different situations due to the differing dynamics of relationships with peers, subordinates, and supervisors (Funder, 1987). Along these lines, Church (1997) found that individuals high in self-monitoring had more agreement with other raters, as they were better at assessing their performance on the job.…”
Section: -3mentioning
confidence: 50%
“…Scholarly research has confirmed these sentiments and found that higher levels of congruence between managerial "self" and "total others" behavioral ratings is associated with managerial effectiveness and performance (Atwater & Yammarino, 1992;Van Velsor, Taylor & Leslie, 1993;Church, 1997). It is also widely believed that this self/total other discrepancy is greater for those who are higher-level managers, although empirical studies have failed to validate this observation (Church, 1997).…”
Section: Feedback: Self/total Others Discrepancy Using Eci 10mentioning
confidence: 75%